The Trumbull lute book c. 1595 - Trumbull, William 1639-1716; Spencer, Robert 1932-1997 (Kilkenny Boethius Press, 1980)
The Trumbull lute book : c.1595 : containing 26 solos, 10 duet parts and 2 mixed consort parts, of which 36 are for 6-course and 2 for 7-course Renaissance lute / with an introductory note and guide to concordances by Robert Spencer.
Keywords: British Library (London, United Kingdom); 16th Century (1501-1600); Lute; Manuscript; United Kingdom